Analisis Penyelesaian Kredit Macet di PNPM-Mandiri: Studi di Desa Mersam, Provinsi Jambi - Kamal Fathoni, M; Umma, Zaimatun; Kurniawan, Ardian; -, Burhanuddin; -, Sulaeman (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
Bad credit is a condition where the customer or debtor is unable to pay his debts at a predetermined time as promised at the beginning of the credit agreement. The problem that occurs is where the disbursed PNPM funds should be used for productive loans or business capital. However, in reality in Mersam Village, Kab. Batanghari Province. Jambi PNPM funds are used by some people for personal needs, causing bad credit, where customers are unable to pay installment payments every month because the funds borrowed are only used for personal needs. This study aims to find out: 1) How to settle bad loans at PNPM Mersam Village, Kab. Batanghari Province. Jambi; 2) How is the settlement of bad loans at PNPM Desa Mersam Kab. Batanghari Province. Jambi from the perspective of Sharia Economic Law. This research is a qualitative research type of empirical legal approach, the types and sources of data used are primary and secondary data. The collection of data used is interviews and documentation. Based on the research conducted, the results of the interviews and the conclusion were obtained that the resolution of bad loans was carried out by PNPM by means of family deliberations and giving an extension of time (rescheduling). In terms of Sharia Economic Law, efforts to settle bad loans in Mersam Village are not contrary to Islamic law, but instead they carry out Islamic law rules in dealing with bad loans that occur in Mersam Village.